Students' perception towards mathematics using APOS Theory: a case study - Daud, Anith Safura; Mohamed Adnan, Nor Syamimi; Abd Aziz, Mohd Kasturi Nor; Embong, Zulmaryan (IOP Publishing, 2020)
Students’ perceptions towards mathematics seem to be shaped by how they define mathematics and the role of mathematics in their life. Most students in Malaysia lack experience in dealing with mathematics, thus their achievement in mathematics are not as good as non-Malaysian students (Liew & Pong, 2004). Therefore, the purpose of this study is to investigate students’ perceptions in learning mathematics and how these perceptions may lead to problems in understanding the mathematics itself among students in selected Malaysian secondary schools. A set of questionnaire was distributed to 200 students in Kuantan, Pahang in order to gauge their perceptions in learning mathematics. The researcher also assesses the relationship that exists between students’ perceptions towards mathematics and their academic achievement by using APOS Theory. The respondents generally reported a positive perception towards mathematics. With regard to the correlation analysis, there was a significant statistical relationship between students’ perceptions towards mathematics and their UPSR mathematics grade. However, there was no significant difference between students’ perception towards mathematics and recent mathematics grade. These results warrant further researches using more advanced statistical tools in order to obtain more accurate and relevant findings. Finally it is hoped that the study will open new paths that can benefit mathematics in education system and how mathematics are perceived by students in the classroom.